Empirical Relationship Between Creativity and Carbon Intensity: A Case of Saudi Arabia - Aziz, Ghazala; Khan, Mohd Saeed (Frontiers in Environmental Science, 2022)
This paper investigates the impact of GDP, renewable energy consumption, patents, and innovation on carbon intensity in Saudi Arabia. For this purpose, we use panel data from 1990 to 2019 and applied pooled OLS with fixed effect and quantile regression techniques to check the long-run association between variables. The results show that GDP is enhancing carbon intensity in Saudi Arabia. However, renewable energy consumption is a significant factor in reducing carbon emission. Further, it is also confirmed that patents and innovation can help reduce carbon intensity in Saudi Arabia. These results are also confirmed through quantile regression analysis. Our results are robust to alternative tests as well. Capital subsidies and feed-in-trade are important policy implications to promote the use of renewable energy.